The Effect of Authentic Reading Material to Enhance Students' Reading Comprehension - Rama, Asri Nofa (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
This study aimed to find out the extent to which authentic material enhance students’ reading comprehension. This study used quasi-experimental design that consists of experimental class and control class. In experimental class referred to the class that is given authentic material. While the control class referred to the class that is given the usual set of conditions or textbook. The study was carried out at Lakidende University of Unaaha and Sembilan belas November University with 60 undergraduates as the sample. Data were collected by using reading test. Moreover, the data were analyzed quantitatively and interpreted by using the software program of SPSS 24.0. This study found that Authentic reading material give a significant effect on students’ reading comprehension from pre-test to post-test revealed the significant difference (0.001 less than 0.05) before and after the implementation of Authentic reading material.